UMP launched MBA Programme beginning February - UMP, PNC
Universiti Malaysia Pahang (UMP) launched its Master's in Business Administration (MBA) programme offered beginning February 2013 that would provide the opportunity to working professionals in the industry especially those in the engineering field to pursue their studies and boost their career and skills in managing their respective organisations.